TIMP-2 mutant decreases MMP-2 activity and augments pressure overload induced LV dysfunction and heart failure. (May 2013) - Givvimani, S.; Kundu, S.; Narayanan, N.; Armaghan, F.; Qipshidze, N.; Pushpakumar, S.; Vacek, T. P.; Tyagi, S. C.
Abstract Pressure overload induces cardiac extracellular matrix (ECM) remodelling and results in heart failure. ECM remodelling by matrix metalloproteinases (MMPs) is primarily regulated by their target inhibitors, tissue inhibitor of matrix metalloproteinases (TIMPs). It is known that TIMP-2 is highly expressed in myocardium and is required for cell surface activation of pro-MMP-2. We and others have reported that imbalance between angiogenic growth factors and anti-angiogenic factors results in transition from compensatory cardiac hypertrophy to heart failure. We previously reported the pro-angiogenic role of MMP-2 in cardiac compensation, however, the specific role of TIMP-2 during pressure overload is yet unclear. We hypothesize that genetic ablation of TIMP-2 exacerbates the adverse cardiac matrix remodelling due to lack of pro-angiogenic MMP-2 and increase in anti-angiogenic factors during pressure overload stress and results in severe heart failure. To verify this, ascending aortic banding (AB) was created to mimic pressure overload, in wild type C57BL6/J and TIMP-2-/- (model of MMP-2 deficiency) mice. Left ventricular (LV) function assessed by echocardiography and pressure-volume loop studies showed severe LV dysfunction in TIMP-2-/- AB mice compared to controls. Expression of MMP-2, vascular endothelial growth factor (VEGF) was decreased and expression of MMP-9, anti-angiogenic factors endostatin and angiostatin was increased in TIMP-2-/- AB mice compared with wild type AB mice. Connexins (Cx) are the gap junction proteins that are widely present in the myocardium and play an important role in endothelial-myocyte coupling. Our results showed that expression of Cx 37 and 43 was decreased in TIMP-2-/- AB mice compared with corresponding wild type controls. These results suggest that genetic ablation of TIMP-2 decrease the expression of pro-angiogenic MMP-2, VEGF and increases anti-angiogenic factors that results in exacerbated abnormal ventricular remodelling leading to severe heart failure.